Progress in antileishmanial drugs: Mechanisms, challenges, and prospects. - Haoran Zhang; Ruixi Yan; Yahui Liu; Mengtao Yu; Ziyi He; Junfeng Xiao; Kaijie Li; Gang Liu; Qin Ning; Yan Li (PLoS Neglected Tropical Diseases)
Leishmaniasis, a neglected tropical disease caused by Leishmania parasites, continues to pose global health challenges. Current treatments face issues like resistance, safety, efficacy, and cost. This review covers the discovery, mechanisms of action, clinical applications, and limitations of key antileishmanial agents: pentavalent antimonials, amphotericin B, miltefosine, paromomycin, and pentamidine. Despite toxicity and resistance (antimonials), hospitalization needs and side effects (amphotericin B), regional efficacy variability (miltefosine), inconsistent outcomes (paromomycin), and severe side effects (pentamidine), these drugs are vital. Novel strategies to overcome the deficiencies of current therapies are highlighted, including combination regimens, advanced drug delivery systems, and immunomodulatory approaches. Comprehensive and cooperative efforts are crucial to fully realize the potential of advancements in antileishmanial pharmacotherapy and to reduce the unacceptable worldwide burden imposed by this neglected disease.